Education for Economic Empowerment: A Community-Based Approach to Enhancing Financial Capability and Household Welfare - I Gusti Kade Heryadi Angligan; Muh. Zuhdy Hamzah; Ni Made Rianita; Lenni Lukitasari; Frederick Saroha Silaban (International Journal of Community Service (IJCS), 2026)
Financial literacy is essential for strengthening household economic resilience and supporting the sustainability of household-based micro, small, and medium enterprises (MSMEs). However, many households continue to face challenges related to limited financial literacy, inadequate financial record-keeping, the mixing of business and household finances, and weak saving habits, all of which hinder effective financial management and long-term welfare. This community service program aimed to enhance financial capability and household welfare through a community-based financial education approach. The program was implemented in one of the banjar in Tonja Village, Denpasar City, Bali, involving 38 participants consisting of Family Welfare Empowerment (PKK) members and household-based MSME entrepreneurs. A participatory approach was employed through preliminary assessment, socialization, interactive training, simulation, practical bookkeeping exercises, mentoring, and evaluation using pre-test and post-test instruments. Five financial literacy indicators were assessed: household budgeting, financial record-keeping, separation of business and household finances, saving behavior, and emergency fund management. The findings revealed significant improvements across all indicators, with the average score increasing from 53.9 in the pre-test to 82.6 in the post-test, representing an overall improvement of 53.3%. The largest improvement was observed in the ability to separate business and household finances (65.8%), while the smallest increase occurred in saving behavior (40.6%). Moreover, 84.2% of participants successfully prepared household budgets, 78.9% consistently maintained financial records, 84.2% correctly calculated simple business profits, and 81.6% improved expenditure management. These findings demonstrate that community-based financial education combined with practical exercises and continuous mentoring effectively enhances financial knowledge, skills, and behavior, thereby contributing to stronger household financial resilience and sustainable economic welfare.